2020
DOI: 10.1002/cam4.3500
|View full text |Cite
|
Sign up to set email alerts
|

Identifying optimal candidates for induction chemotherapy among stage II–IVa nasopharyngeal carcinoma based on pretreatment Epstein–Barr virus DNA and nodal maximal standard uptake values of [18F]‐fluorodeoxyglucose positron emission tomography

Abstract: Objective This study aimed to select optimal candidates benefiting from the addition of induction chemotherapy (IC) to concurrent chemoradiotherapy (CCRT) in stage II–IVa nasopharyngeal carcinoma (NPC) based on Epstein–Barr virus (EBV) DNA and nodal maximal standardized uptake values (SUVmax‐N) of [ 18 F]‐fluorodeoxyglucose positron emission tomography. Patients and materials A total of 679 patients diagnosed with stage II–IVa (except N0) NPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Thus, recent studies emphasize selecting effective biomarkers to identify ideal candidates for IC. NPC patients with higher pre-treatment plasma EBV DNA level content reportedly benefit more from the IC administration (10), consistent with our data that the IC + CCRT group tended to have higher plasma EBV DNA loads. However, whether HBV infection is a prognostic factor for IC has not been widely investigated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, recent studies emphasize selecting effective biomarkers to identify ideal candidates for IC. NPC patients with higher pre-treatment plasma EBV DNA level content reportedly benefit more from the IC administration (10), consistent with our data that the IC + CCRT group tended to have higher plasma EBV DNA loads. However, whether HBV infection is a prognostic factor for IC has not been widely investigated.…”
Section: Discussionsupporting
confidence: 91%
“…However, not all patients with NPC benefit from this therapy (7,8). Furthermore, considering the side effects, time, and economic cost of IC, many researchers have screened for biomarkers to optimize clinical decision-making (9)(10)(11)(12)(13)(14). Serological hepatitis B surface antigen (HBsAg) is an important indicator of hepatitis B virus (HBV) infection, but whether HBsAg can be used as a reference factor in the choice of IC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that the addition of IC was associated with more acute toxicities, which is similar to previous studies. 10 , 13 In that case, there is an urgent need for a more comprehensive prognostic model to precisely predict patient clinical survival and guide individualized treatment based on risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the addition of IC was associated with more acute toxicities, which is similar to previous studies. 10,13 In that Patients with a higher risk of treatment failure are generally considered to benefit more from additional IC. Several studies followed up on this experience and confirmed the benefit of IC in NPC patients with high risk through the prognostic models they built.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation